3D Real-Time Reconstruction using the Cloud - Riazuelo, L.; Civera, J.; Montiel, J.M.M. (Jornada de Jóvenes Investigadores del I3A, 2017)
This work presents a 3D real-time reconstruction based on a visual SLAM (Simultaneous Localization and Mapping) approach using a RGBD camera. The proposed system aims to create a 3D model of an environment using a low-power computer and Amazon EC2 (Elastic Compute Cloud) server for computation offloading.